A value-added nutribar made from underutilized green seaweed Ulva lactuca from Sri Lanka - Udayangani, R.M.A.C.; Wijesekara, I.; Wickramasinghe, I.; Jayasinghe, M.A. (My University, 2017)
attached

Edible seaweeds have been consumed and used in Traditional Medicine for centuries by East Asian people. However, in Sri Lank, these seaweeds are underutilized and they have potential to develop novel nutraceutical food products. Four species of edible green seaweeds (Ulvalactuca, Ulvacompressa, Caclerparacemosa, and Choetomorphaantennina) were manually collected from the Southern Coast, Matara, Sri Lanka. The crude protein contents of the above powdered seaweeds and proximate composition of U. lactuca were determined by Kjeldhal and AOAC methods, respectively. Furthermore, cereal-based nutibars incorporated with 0, 5, and 10% of dried U. lactuca (w/w) were developed. In addition, their textural properties, crude potein contents and antioxidant activities were investigated. Results showed that U. lactuca showed significantly (at p ≤ 0.05) the highest crude protein content (2.16 ± 1.07%) followed by Caclerparacemosa (16.90 ± 0.35%) Choetomorphaantennina (16.25 ± 0.13%) and Ulvacompressa (7.69 ± 1.08%). The mineral and crude lipid contents of U. lactuca were 17.17 ± 0.62% and 1.37 ± 0.05% respectively. Interestingly, the U. lactuca 5% enriched nutribar was shown almost similar in sensory and textural profiles, except for colour, compared to the control (0%). Under-utilized U. lactuca in Sri Lanka can be processed to develop novel healthy and nutritious foods. Moreover, promoting seaweeds utilization will improve the life style of coastal families by generating an additional income.
Keywords: Sea weeds; Traditional medicine; Ulvalactuca; Proteins; Nutribar